Editorial Comment - Olujobi, Olusola Joshua (Journal of Sustainable Development Law and Policy, 2024)
The Journal of Sustainable Development Law and Policy is a peer- reviewed interdisciplinary journal published by the Institute for Oil, Gas, Energy, Environment and Sustainable Development, Afe Babalola University, Ado Ekiti, Nigeria. It is published in June and October by the Afe Babalola University Press, Nigeria.